(untitled) (Research, Society and Development, 2020)
Objective: to understand the expectations that the puerperal women have in relation to labor and delivery and, what are the feelings that the peripartum period aroused in these women. Methodology: qualitative study, carried out in a teaching hospital in southern Brazil, whose inclusion criteria were: postpartum women who had low-risk pregnancies and who went through labor and vaginal delivery. And, the exclusion criteria: women who had complications during labor, a cesarean section indicated during or, after delivery, were not with their babies. Data collection took place through semi-structured interviews and analyzed using Content Analysis. Results: After the analysis, a category emerged: The mothers perception about labor and delivery, which was divided into two subcategories: Expectations about labor and delivery and feelings related to labor and delivery. It was possible to perceive women’s unpreparedness and lack of knowledge about the birth process, reports of positive, but superficial expectations and negative feelings, such as suffering, fear, pain, anxiety, demonstrating an important failure in prenatal care. Conclusion: It is concluded that there is disinformation among women about the complexity of giving birth, which removes their power of decision and autonomy over childbirth.